Tetracycline Resistance Genes Identified from Distinct Soil Environments in China by Functional Metagenomics - Wang, Shaochen; Gao, Xia; Gao, Yuejiao; Li, Yanqing; Cao, Mingming; Xi, Zhenhua; Zhao, Lixing; Feng, Zhiyang (Frontiers in Microbiology, 2017)
Soil microbiota represents one of the ancient evolutionary origins of antibiotic resistance and has been increasingly recognized as a potentially vast unstudied reservoir of resistance genes with possibilities to exchange with pathogens. Tetracycline resistance is one of the most abundant antibiotic resistances that may transfer among clinical and commensal microorganisms. To investigate tetracycline resistance genes from soil bacteria in different habitats, we performed functional analysis of three metagenomic libraries derived from soil samples collected from Yunnan, Sichuan and Tibet, respectively, in China. We found efflux transporter genes form all the libraries, including twenty one major facilitator superfamily (MFS) efflux pump genes and one multidrug and toxic compound extrusion (MATE) transporter gene. Interestingly, we also identified two tetracycline destructase genes, belonging to a newly described family of tetracycline-inactivating enzymes that scarcely observed in clinical pathogens, from the Tibet library. The inactivation activity of the putative enzyme was confirmed in vitro by biochemical analysis. Our results indicated that efflux pumps distributed predominantly across habitats. Meanwhile, the mechanism of enzymatic inactivation for tetracycline resistance should not be neglected and merits further investigation.